1999
DOI: 10.1038/sj.bjc.6690632
|View full text |Cite
|
Sign up to set email alerts
|

p53 protein, EGF receptor, and anti-p53 antibodies in serum from patients with occupationally derived lung cancer

Abstract: The oncogene product epidermal growth factor receptor (EGF-R), the tumour suppressor gene product p53 and anti-p53 antibodies are detectable in the serum of certain cancer patients. Increased levels of some of these products were reported in lung cancer patients after occupational asbestos exposure and after exposure to polycyclic aromatic hydrocarbons or vinylchloride. In the first step, this study investigated the possible diagnostic value of serum EGF-R, p53-protein and anti-p53 antibodies, measured by an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Moreover, there was a significant correlation between increased EGFR levels, both in serum and tissues, as well as EGFR gene amplification and T-stage, which is considered a surrogate prognostic factor in MPM. Our results are comparable to those of Betta et al [21] and Schneider et al [22] who found no differences in serum values of EGFR between MPM patients with varied clinical outcomes and attributed this to the small number of cases studied. In the present study, there was a trend for patients with low serum EGFR levels to show better response to treatment compared to those with high serum EGFR >0.23 ng/dl as a cutoff value separating patients from healthy controls though the difference did not reach a statistically significant value (p = 0.09).…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, there was a significant correlation between increased EGFR levels, both in serum and tissues, as well as EGFR gene amplification and T-stage, which is considered a surrogate prognostic factor in MPM. Our results are comparable to those of Betta et al [21] and Schneider et al [22] who found no differences in serum values of EGFR between MPM patients with varied clinical outcomes and attributed this to the small number of cases studied. In the present study, there was a trend for patients with low serum EGFR levels to show better response to treatment compared to those with high serum EGFR >0.23 ng/dl as a cutoff value separating patients from healthy controls though the difference did not reach a statistically significant value (p = 0.09).…”
Section: Discussionsupporting
confidence: 94%
“…6). Comparison of pooled diagnostic parameters using all studies or all studies except for three outliers [33,36,37] showed that excluding the three studies reduced sensitivity from 0.19 to 0.17, DOR from 10 to 9 and PLR from 8.6 to 7.9, whereas it increased NLR from 0.83 to 0.85 and AUC from 0.82 to 0.91. Specificity in both cases was 0.98.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…20 Serum EGFR has been the topic of relatively few reports, and the results from those studies are conflicting. In 2 studies, no significant difference was reported in serum EGFR levels between a healthy control group and patients with lung cancer 30 or patients with squamous cell carcinoma of the head and neck. 31 Some investigators identified significantly elevated levels of serum EGFR both in patients with cervical carcinoma and in patients with carcinoma in situ compared with healthy controls, 32 whereas other investigators reported significantly elevated levels of serum EGFR in patients who had lymph node-positive lung cancer compared with the levels in patients who had lymph node-negative lung cancer, but no significant difference was reported in serum EGFR levels between patients with lung cancer and a control group of patients with nonmalignant disease.…”
mentioning
confidence: 99%